2021
DOI: 10.1111/geb.13422
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen dynamics in tropical ecosystems following fire

Abstract: Aim: Tropical ecosystems have grown increasingly prone to fire over the last century.However, no consensus has yet emerged regarding the effects of fire disturbances on tropical biogeochemical cycles.Location: Tropics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 80 publications
(191 reference statements)
0
2
0
Order By: Relevance
“…Natural processes (e.g., fire and grazing) impact N cycling in land ecosystems, and these processes are independent of legume effects but are dependent on ecosystem types and/or climatic regions. Frequent fire and disturbances (e.g., grazing) significantly change the cycling and availability of N (Dannenmann et al, 2018; Jiang et al, 2022) and can also remove large quantities of N from unmanaged ecosystems, which stimulates rapid regeneration of N‐fixing species and individuals to replenish N deficits (Batterman et al, 2013; Vitousek et al, 2013). For example, Batterman et al (2013) found that N‐fixers dynamically act to replenish N deficits caused by disturbance events in tropical forests and soils.…”
Section: Discussionmentioning
confidence: 99%
“…Natural processes (e.g., fire and grazing) impact N cycling in land ecosystems, and these processes are independent of legume effects but are dependent on ecosystem types and/or climatic regions. Frequent fire and disturbances (e.g., grazing) significantly change the cycling and availability of N (Dannenmann et al, 2018; Jiang et al, 2022) and can also remove large quantities of N from unmanaged ecosystems, which stimulates rapid regeneration of N‐fixing species and individuals to replenish N deficits (Batterman et al, 2013; Vitousek et al, 2013). For example, Batterman et al (2013) found that N‐fixers dynamically act to replenish N deficits caused by disturbance events in tropical forests and soils.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial community composition analyses revealed Proteobacteria as the most dominant phyla in all the twenty sites. Proteobacteria is a common inhabitant in agricultural soils with many studies reporting them as dominant phyla in the rhizosphere ( Rascovan et al., 2016 ; Jiao et al., 2019 ; Bziuk et al., 2021 ) and highlighting their role in biogeochemical cycles of nitrogen and carbon ( Jiang et al., 2022 ). The other major phyla identified in the wheat rhizosphere under present study are Chloroflexi, Actinobacteria, Acidobacteria, Bacteroidetes, Gemmatimonadetes, Verrucomicrobia, Planctomyces, Firmicutes, Cyanobacteria, and Nitrospirae.…”
Section: Discussionmentioning
confidence: 99%